A longitudinal observational population-based study of brain volume associated with changes in sleep timing from middle to late-life. Issue 4 (10th November 2020) - Kim, Regina E Y; Kim, Hyeon Jin; Kim, Soriul; Abbott, Robert D; Thomas, Robert J; Yun, Chang-Ho; Lee, Hyang Woon; Shin, Chol
Abstract: Study Objectives: Sleep behaviors are related to brain structure and function, but the impact of long-term changes in sleep timing on brain health has not been clearly addressed. The purpose of this study was to examine the association of longitudinal changes in sleep timing from middle to late-life with gray matter volume (GMV), an important marker of brain aging. Methods: We enrolled 1798 adults (aged 49–82 years, men 54.6%) who underwent magnetic resonance imaging (MRI) between 2011 and 2014. Midsleep time (MST) on free days corrected for sleep debt on workdays was adopted as a marker of sleep timing. Data on MST were available at the time of MRI assessment and at examinations that were given 9 years earlier (2003–2004). Longitudinal changes in MST over the 9-year period were derived and categorized into quartiles. Subjects in quartile 1 were defined as "advancers" (MST advanced ≥ 1 h) while those in quartile 4 were defined as "delayers" (MST delayed ≥ 0.2 h). Quartiles 2–3 defined a reference group (MST change was considered modest). The relationship of GMV with MST changes over 9 years was investigated. Results: Nine-year change in MST were significantly associated with GMV. Compared to the reference group, advancers had smaller GMVs in the frontal and temporal regions. A delay in MST was also associated with smaller cerebellar GMV. Conclusions: In middle-to-late adulthood, the direction of change in MST is associated with GMV. While advancers and delayers in MST tend to present lower GMV, associations appear to differ across brain regions.